Multiparameter analysis of Diuron and its metabolites (DCA and DCPMU) in different stages of zebrafish (Danio rerio) development - Peixoto, Paloma Vitória Lima [UNESP]; Sales, Bianca Camargo Penteado [UNESP]; Aggio, Luiza [UNESP]; Viriato, Cristina; Pereira, Lilian Cristina [UNESP] (Frontiers, 2024)
Introduction: Diuron (3-(3,4-dichlorophenyl)-1,1-dimethylurea) is a prominent herbicide in Brazilian agriculture, particularly in sugarcane farming. This herbicide persists in the environment and is transformed into potentially toxic metabolites, such as 3,4-dichloroaniline (DCA) and 3-(3,4-dichlorophenyl)-1-methylurea (DCPMU), raising concerns that encompass environmental contamination and One Health, which unites environmental and human health. Zebrafish are an appropriate experimental model to evaluate toxicity: they metabolically and genetically resemble humans and can be applied in ecotoxicology. Methods: In this study, we have employed multiparameter evaluation to characterize the toxicity of environmentally relevant concentrations (0.5–100 μM) of Diuron, DCA, or DCPMU in Brazil, a developing country. In the early stages of zebrafish development, we performed the fish embryo toxicity test according to the guidelines established in OECD Protocol No. 236, extended to 144 h post fertilization (hpf). We also investigated the oxygen consumption rate in zebrafish embryos at 24 hpf, evaluated the acetylcholinesterase (AChE) enzymatic activity in zebrafish larvae at 96 hpf, and used the Comet Assay to assess DNA fragmentation in zebrafish larvae at 96 hpf. We subjected adult zebrafish to acute exposure for 96 h in accordance with OECD protocol no. 203 for the Acute Toxicity Test in Fish. Following this exposure, we analyzed mutagenicity by using the micronucleus test, which was complemented by quantification of nuclear anomalies (NA) in erythrocytes and further confirmed by histopathological investigations. Results and discussion: Exposure to any of the tested Diuron concentrations damaged DNA, and NA became significant beyond 10 μM Diuron. At 10 μM, DCA altered AChE activity, suggesting neuromuscular toxicity. Between 0.5 and 5 μM, DCA was potentially genotoxic, and 5–10 μM DCA induced nuclear pleomorphism. At all the tested concentrations, DCPMU damaged DNA, and NA emerged between 1 and 10 μM DCPMU. Adult zebrafish exposed to any of the tested Diuron, DCA, or DCPMU concentrations for 96 h did not exhibit significant histopathological alterations. Erythrocyte morphology analysis did not reveal mutagenicity. Although we observed non-mutagenic genotoxicity, chromosomal instability is of concern. The findings of this study contribute to our understanding of how Diuron and its metabolites affect zebrafish and highlights the need for multiparametric assessment to elucidate how herbicides and their metabolites impact the environment and human health. This endeavor informs regulatory measures for safely using Diuron and similar herbicides and reveals substantial implications for developing nations grappling with escalating water contamination due to pesticide use.
Keywords: acetylcholinesterase activity; embryotoxicity; genotoxicity; histopathology; mutagenicity